2007
DOI: 10.1111/j.1551-2916.2007.01993.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Finite Element Study of the Thermal Conductivity of α‐SiAlON Ceramics

Abstract: The thermal conductivity of monolithic Y‐Sm/α‐SiAlON was evaluated using experimental data and finite element analysis. The thermal diffusivities of Y, Y‐Dy, and Y‐Ce/α‐SiAlON ceramics were also investigated experimentally for comparison. The maximum achievable thermal conductivity of Y‐Sm/α‐SiAlON has been calculated by the linear extrapolation of the temperature‐based experimental inverse diffusivity data and was used for the numerical calculations. Two‐dimensional model microstructures were built on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…The results show that the density, hardness, modulus of elasticity, flexural strength and thermal expansion coefficient of β-SiAlON decreased with an increase in the Z value [6]. It has been reported that, compared to α-SiAlON, β-SiAlON exhibits enhanced fracture toughness and strength as well as high thermal conductivities and thermal shock resistance due to the rod-shaped grain structure [7,8]. Because of its outstanding mechanical and thermal properties at high temperatures, and its excellent chemical stability and thermal shock resistance, β-SiAlON has been attracting considerable attention as an important high-temperature resistant ceramic [9][10][11][12].…”
Section: Introductionmentioning
confidence: 92%
“…The results show that the density, hardness, modulus of elasticity, flexural strength and thermal expansion coefficient of β-SiAlON decreased with an increase in the Z value [6]. It has been reported that, compared to α-SiAlON, β-SiAlON exhibits enhanced fracture toughness and strength as well as high thermal conductivities and thermal shock resistance due to the rod-shaped grain structure [7,8]. Because of its outstanding mechanical and thermal properties at high temperatures, and its excellent chemical stability and thermal shock resistance, β-SiAlON has been attracting considerable attention as an important high-temperature resistant ceramic [9][10][11][12].…”
Section: Introductionmentioning
confidence: 92%
“…The Sialon PCP may overcome the above mentioned limitations that limit the other PCPs for extreme high brightness lighting. The α-Sialon ceramics has thermal conductivity around 12 -19 Wm −1 K −1 , which makes the material appropriate for extreme high brightness lighting [11,32].…”
Section: Functional Transparent / Translucent Sialon Ceramicsmentioning
confidence: 99%
“…In order to obtain dense materials, Ilmars Zalite et al [8] prepared α-and α-/β-Sialon composites using five plasma-synthesized nanopowders such as Si 3 N 4 , the mixture of 90%Si 3 It has been reported that β-Sialon exhibited enhanced fracture toughness and strength as well as high thermal conductivities compared to α-Sialon due to their rod shape grain structure [9,10]. In addition, β-Sialon showed nontoxicity, good electrical insulation and thermal shock resistance properties, which enabled it to be a promising candidate for high-speed circuits and power devices as heat dissipation and packaging material [11].…”
Section: Introductionmentioning
confidence: 99%